Farmer suicides in India and the weather god - Nilanjan Banik; Philip Stevens (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2016)
This paper examines the reasons for farmer suicides in India. Inability to get the right price, crop failures, and insurmountable debt are the factors that may drive the farmers to take this extreme step. A key factor for farmers being unable to get market prices is inefficient agriculture supply chain management. We find that the reasons for inefficient supply chain management include lack of reforms in the Agricultural Produce Market Committee (APMC) Act, low bargaining power due to small farm size, and lack of warehousing facilities. Crop failures happen because of poor irrigation facilities. Considering agricultural output and rainfall data from four different states in India we find evidence in favor of association between the cyclical component of agricultural output and rainfall data. Understanding this linkage is important from the perspective of formulating demand management policies (read, intervention by the government and central bank).
Keywords: C50; E31; E32; 330; Agriculture output; Beveridge-Nelson Decomposition; APMC Act; Rainfall; India